2013
DOI: 10.1371/journal.pone.0075378
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Process Management and In-Hospital Delays in Treatment with iv Thrombolysis

Abstract: ObjectivesRapid initiation of intravenous thrombolysis improves patient’s outcome in acute stroke. We analyzed inter-center variability and factors that influence the door-to-needle time with a special focus on process measurements in all Austrian stroke units.MethodsCase level data of patients receiving intravenous thrombolysis in the Austrian Stroke Unit Registry were enriched with information of a structured questionnaire on center specific process measures of all Austrian stroke units. Influence of case an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
3
15
0
1
Order By: Relevance
“…Similar to our data, previous studies have shown that older patients receive less often anticoagulation if they experience atrial fibrillation 5,6 and more often a swallow screening. 7 This might be because of the fact that older age is associated with more severe strokes being associated with higher risk of complications.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our data, previous studies have shown that older patients receive less often anticoagulation if they experience atrial fibrillation 5,6 and more often a swallow screening. 7 This might be because of the fact that older age is associated with more severe strokes being associated with higher risk of complications.…”
Section: Discussionsupporting
confidence: 92%
“…Arrival by emergency medical services was associated with improved DAT and DIT, 7,8 and patient factors such as blood pressure, blood glucose, National Institutes of Health Stroke Scale score of >2, intubation/high oxygen requirement, and sex were found to be significant factors that predicted activation and imaging times. [8][9][10] Interestingly, time cycle factors were significant in our study, contrasting previous research showing no association between DIT and time of day or day of week. 19 The underlying mechanism is not clear, but time may be a surrogate for ED crowding, given the cyclic nature of ED patient arrivals and patient volumes.…”
Section: Strokementioning
confidence: 93%
“…5,6 Mode of patient arrival (emergency medical services versus private vehicle) is another care process known to affect DIT. 7,8 In addition, patient-specific factors, including sex, symptom severity, symptom duration, history of diabetes mellitus, and initial blood pressure, also are reported to affect DIT. [8][9][10] Although research related to DIT in stroke is extensive, it has focused primarily on process-specific and patient-specific factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its widespread immediate availability, CT remains the most common and the first line imaging modality used in acute ischemic stroke (18). It is used to rule out hemorrhagic strokes (e.g., intracerebral hemorrhage (ICH)).…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%